Temporal disaggregation of rainfall for Singapore - Ong, Kathy Yajuan. (2013)
This report serves as a recount on the Final Year Project the author undertook during full two semesters in her fourth year undergraduate study in Nanyang Technology University (NTU). The final year project is an integral part of an NTU student’s graduation requirement in the last year of study in the college.